The Second Canonization of the Qurʾān (324/936) : a Ibn Mujāhid and the Founding of the Seven Readings - Nasser, Shady (BRILL, 2020)
In The Second Canonization of the Qurʾān , Nasser studies the transmission and reception of the Qurʾānic text and its variant readings through the work of Ibn Mujāhid (d. 324/936), the founder of the system of the Seven Eponymous Readings of the Qurʾān. The overarching project aims to track and study the scrupulous revisions the Qurʾān underwent, in its recited, oral form, through the 1,400-year journey towards a final, static, and systematized text. For the very first time, the book offers a complete and detailed documentation of all the variant readings of the Qurʾān as recorded by Ibn Mujāhid. A comprehensive audio recording accompanies the book, with more than 5,000 audio files of Qurʾānic recitations of variant readings.